A review of bio-inspired geotechnics-perspectives from geomaterials, geo-components, and drilling & excavation strategies - Wengang Zhang; Jiaying Xiang; Ruijie Huang; Hanlong Liu (Biogeotechnics)
As urbanization progresses, the demand for high-rise buildings and underground spaces is growing, and the need for firm geotechnical construction materials, efficient excavation methods, accurate testing instruments, and innovative geotechnical engineering theories and technologies is increasing. By investigating the phenomena of strengthening and toughening in nature, hydrophobic and ice-phobic, friction anisotropy and drilling as well as excavation, etc, researchers have found that organisms have distinctive external morphology and organization. By imitating the external morphology, structural characteristics or movement mechanism of organisms, novel ideas, new principles, and innovative theories can be provided for the innovation and sustainable development of geotechnical engineering. This paper mainly expounds on the bio-inspired application in geotechnical engineering from three perspectives: geo-materials, geotechnical components, and drilling & excavation equipment, and lists typical application cases. In conclusion, this paper presents a summary and prospects of bio-inspired geotechnical engineering, offering fundamental insights for future research.